Oil palm genetic origins, pollinator insect and environmental factor effect on fruit set ratio and yield components under tropical peat soil - Senesie, Swaray (2021)
Oil palm industry in Malaysia has been facing a declining trend in fruit set and oil yield. To determine the major factors causing the decline, a comprehensive study was carried out by investigating the performance of parental dura (D) and pisifera (P) genetic origins on their biparental D×P progenies, pollinator insect and environmental factors. The planting materials used in this study consisted of 24 D×P progenies developed through biparental breeding design. Genetic origins comprised of six female duras (Deli Serdang, Tanzania, Angola, Deli Ulu Remis, Deli Johor Labis and Deli Banting) and four male pisiferas (Cameroon, Algenene-vereniging rubber planters (AVROS), Nigeria and Yangambi) were hybridized by Malaysian Palm Oil Board (MPOB). The research was conducted at MPOB Research Station, Teluk Intan, Perak. The trial was established in September 2008 in an independent complete randomized design (ICRD) with a triangular planting distance of 8.5 meters on 12.06 hectares with 1930 palms. Data collection on yield and fruit bunch characteristics were carried out as well as inflorescence sex ratio (ISR), fruit set ratio (FSR), Elaeidobius kamerunicus (EK) population size and climatic data. Analysis of variance showed that there was greater genetic variability among the D×P progenies. Progeny ECPHP500 produced the highest fresh fruit bunch (FFB, 184.62 kg palm-1yr-1 ). Progenies PK4674 and PK4465 had the highest FSR at 61.12 and 60.93%, respectively. The highest oil yield (POY) was recorded from progeny PK4674 with 52.66 kg palm-1yr-1 . By using an unweighted pair-group procedure with arithmetic mean (UPGMA) and principal components analysis (PCA), the 24 progenies were grouped into seven different clusters. For fruit bunch quality traits, including FSR and POY found that progeny PK4674 was the most outstanding among other progenies. The ‘S-shape” technique in determining fruit set showed that PK4674 had the highest FSR (65.78%). Analysis of variance also exhibited that ISR influenced the decline in FSR among the progenies and their parental lines. PK4841 recorded with highest male flower production at 5.85 palm-1 year-1 . The analysis of variance also showed the occurrence of variability in EK populations and efficiency among the progenies. Also, the present study indicated a decline in EK population force and efficiency, only three progenies (PK4674, PK4465 and PK4482) were above 60% critical level of FSR. Among the genetic origins, Deli Banting × AVROS recorded the highest population force of EK, but Deli Ulu Remis × AVROS had the highest fruit to bunch (FTB) and FSR. Regression analysis indicated that the relationships of EK population with average bunch weight (ABW), fertile fruit (FF), FTB, ISR and FSR were found to be moderate, where the EK accounted for 25% of the variation in ABW, 37% in FF, 31% in FTB, 26% in ISR and 33% in FSR. The regression results showed that oil to bunch (OTB) was observed to be the highest contributor to POY followed by mesocarp to fruit (MTF) and FFB. Low EK population especially male weevils were observed to be the major factor in FSR decline, followed by wind velocity and field temperature. The findings from this study recommended that Deli Ulu Remis  AVROS, and progeny PK4674 were selected for production of the superior D×P planting materials with high fruit set ratio and oil yield traits.